Perancangan Sistem Manajemen Mutu ISO 9001:2015 pada CV. XYZ - Vincenzio Randy Sumawan; Jani Rahardjo (Jurnal Titra, 2022)
CV. XYZ is a company engaged in the food industry which is located in Makassar and was founded in 2009. The company does not yet have documents that are in accordance with ISO 9001:2015. This study aims to design a quality management system based on ISO 9001:2015 in CV. XYZ. The design is done by completing the documents that are not owned by the company. The initial research was conducted using gap analysis through interviews with the company. The results of the initial gap analysis show that the company only meets the percentage of completeness of documents by 3% and after the preparation and completion of the company's vision and mission documents, SWOT analysis, quality objectives, risk identification, preparation of SOPs and other documents. The results of the gap analysis ended that the company had an average percentage of document completeness of 84% which increased by about 81% of document completeness.